The influence of organizational culture and leadership on principal’s organizational commitment - Nurlina Nurlina; Meilia Rosani; Neta Dian Lestari; Reva Maria Valianti; Muhammad Kristiawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to analyze the influence of organizational culture and leadership on the principal's organizational commitment The method used in this research is a survey method. The unit of analysis in this study is the principal of the elementary school. The analytical technique used is path analysis using Lisrel Software. The sample of this research includes principals of public elementary schools who meet the predetermined criteria, with a total sample of 90 principals and 90 teachers. The results showed that organizational culture and leadership had a direct positive effect on organizational commitment, which was 0.31. This means that there is a direct positive influence of organizational culture and leadership on organizational commitment because the value of tcount = 3.09 > ttable = 1.988. The coefficient of this path is marked alpha 5%, meaning that this hypothesis is proven, thus the organizational culture and leadership variables have a direct positive effect on the organizational commitment variable. This means that culture and leadership directly affect the commitment of organizational leaders in the city of Palembang. A person's organizational suitability has a strong positive direct influence on a commitment to the organization, members who are in the organization have a high level of effectiveness towards the organization.